ANALYSIS OF MATHEMATIC CONNECTION ABILITY ON TRIANGLE AND QUALITY MATERIAL WITH REALISTIC MATHEMATICS EDUCATION APPROACH FROM SELF ESTEEM STUDENTS OF CLASS VII SMPS MUHAMMADIYAH 1 MEDAN ACADEMIC YEAR 2021/2022 - Adinda Sahira; M. Amin Fauzi (International Journal Labs, 2022)
This study aims to determine the completeness of students' learning outcomes with mathematical connection abilities through a realistic mathematics education approach, to find out how students' self-esteem is in learning mathematics, and to determine students' mathematical connection abilities based on the categories of high, medium, and low self-esteem obtained. This type of research is a qualitative research with a descriptive approach. The study was conducted in Class VII Integrated 4 SMPS Muhammadiyah 1 Medan with a total of 35 students. The instrument used is a mathematical connection ability test, self-esteem questionnaire and interview with selected subjects with 1 student in the high self-esteem category, 2 students in the medium category and 3 students in the low category. The results showed: 1) The classical completeness of the learning outcomes test was 88.5%. 2) the results of self-esteem of students who have high self-esteem are 5 students, moderate self-esteem are 24 students and low self-esteem are 6 students. 3) Students' mathematical connection abilities in Integrated 4th grade VII in three categories, including high self-esteem in learning mathematics with a realistic mathematics education approach, students fulfill all indicators of mathematical connection ability. In the moderate self-esteem category, students meet two indicators of mathematical connection ability well but are less than perfect on one indicator. And at low self-esteem students are less able to meet the three indicators well